Women's economic advancement through agricultural change: a review of donor experience - Peña, Christine; Webb, Patrick; Haddad, Lawrence J. (International Food Policy Research Institute, 1996)
This paper reviews donor experience with the design of development projects that are sensitive to gender-specific constraints. The review finds that the gap between intentions and implementation as regards gender-sensitivity is larger in agriculture than in health and nutrition. One of the reasons forwarded for this gap is the dearth of quantitative studies documenting the foregone benefits in terms of agricultural productivity of not promoting the economic advancement of women in agriculture.